Rastin Certificate Market (RCM):A Complementary System of Rastin Banking - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
New financial instruments as Rastin Certificates and Rastin Swap Bonds are used in Rastin banking. Rastin Certificate Market (RCM) provides necessary conditions for transaction and transfer of these instruments based on information technology and the integrated Rastin banking subsystems. This market is accessible for electronic account holders on the World Wide Web.